Application of Gibbs Framework Reflection Method in Elementary School Sports Teachers Community - Ridwan, Ridwan; Hamid, Muliyadi; Suyuthi, Nurmadhani Fitri (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This research was conducted in the community of the PJOK Subject Teacher Working Group in Penajam District, Penajam Paser Utara Regency. accompanied by (Mulyadi Hamid and Nurmadhani Fitri). The application of reflection management using the Gibbs framework, with the aim of knowing the improvement of sports teacher competence by using 6 reflection flows of the Gibbs Framework consisting of Description, Feeling, Evaluation, Analysis, Conclusion, and Follow-up Plan. The approach used in this research is a descriptive qualitative approach with the aim of getting a clear picture of the data analysed in the form of real facts in the field in the form of observation results, interviews and supporting documentation obtained from the informants studied. The results of the research on the application of the Gibbs reflection framework have a positive impact on PJOK teachers, where Gibbs Reflection can improve teachers' professional skills, self-awareness, and ability to manage the classroom better. The impact on learners can be observed from the effectiveness, engagement, understanding, skills, and confidence of learners. The continuous reflection process enables teachers to continuously develop their competence, create effective learning, and support learners' overall development.